Digital Pragmatism in Education: Reconstructing Learning Paradigms through Sociological Lens of Digital Platforms - Mesra, Romi; Jamaris, Jamaris; Sufyarma, Sufyarma (Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2024)
This study aims to explore digital pragmatism in education through sociological and philosophical lenses, focusing on the reconstruction of learning paradigms in the digital era. Qualitative literature study methods are used to analyze epistemological, pedagogical, and structural transformations in the digital ecosystem. The study uses an interdisciplinary approach, exploring theories from digital sociology, the philosophy of pragmatism, social constructivism, and critical theory. The main findings show that digital platforms are not just a medium, but a complex social space that shapes and is shaped by knowledge practices. Digital pragmatism gives rise to a network epistemology model, transforms the role of educators, and opens up a multi-perspective negotiation space for meaning. The study recommends the development of a responsive pedagogical framework, critical digital literacy, and an interdisciplinary approach in understanding the dynamics of educational technology. The theoretical and practical implications of this study contribute to a comprehensive understanding of educational transformation in the digital era.